Bundled solution for smart seeds and market system for smallholders in Ghana - Obeng Adomaa, Faustina (2025)
3. This infographic presents strategic partnership among small and medium scale agricultural enterprises supported with technical assistance from AICCRA through the Council of Scientific and Industrial Research- Crops Research Institute of Ghana (CSIR-CRI) leading to the development and deployment of bundled smart seeds and market systems solution for maize and cowpea. This bundle enabled smallholder farmers build resilience and improve availability of major staples in Ghana.